ANALYSIS OF MATHEMATICS QUESTIONS ON THEME 9 AT GRADE V OF RAUDHATUL RAHMAH ISLAMIC ELEMENTARY SCHOOL PEKANBARU - Eni Siskowati; Syahrul Ramadhan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses learning evaluation through test techniques, which are conducted on fifth-grade elementary school students on Mathematics learning subjects. The research is a type of quantitative descriptive research using the ex post facto method. The instrument used was 20 items of math subject matter questions, which were collected through a written test technique on students. The data obtained were analyzed using the Rasch Model assisted by the Winstep program through an empirical validity process, which includes validity, reliability, and difficulty level tests. The results indicate that in the validity test, items were invalid. In the reliability test, there were 2 reliabilities, Person Reliability was categorized as very good and Item Reliability was categorized as weak. Whereas on the results of the question difficulty level was categorized as very difficult. The implication of the research is that the research can be a reference for other researchers in conducting research on identifying and analyzing question items. When designing the questions, it is expected that a review will be carried out regarding the material that will be discussed on the test.